UJI AKTIVITAS ANALGESIK EKSTRAK KULIT PISANG KEPOK (Musa paradisiaca L.) PADA MENCIT JANTAN (Mus musculus) - Oktavia Nia Agustin; Asri Wido Mukti; Dewi Perwito Sari (Klinikal Sains : Jurnal Analis Kesehatan, 2024)
Unpleasant multidimensional sensory experience When tissue is damaged is the meaning of pain. However, the pain can be managed by taking painkillers, but the use of painkillers causes several side effects, one of which is stomach irritation. Banana plants are an alternative that is widely used to produce medicine from natural ingredients. Kepok banana peels are waste that has not been utilized optimally. With 5 groups each consisting of 5 mice, this study used the hot plate method to evaluate the analgesic activity of kepok banana peel extract (Musa paradisiaca L.) in male mice (Mus musculus). These groups included the negative control group (CMC Na 0.5%), positive control group (Diclofenac sodium 0.13 mg/20 gBW), and kepok banana peel extract group (1000 mg/kgBW, 2000 mg/kgBW, and 3000 mg/kgBW). The results of the research showed that kepok banana peel extract (Musa paradisiaca L.) had analgesic activity on male mice (Mus musculus) utilizing the Rapid Heating technique, the % MPE value for Kepok Banana Peel Extract (1000 mg/kg BW) of 19.33%, Banana Peel Extract Kepok (2000 mg/kg BB) of 40.43%, and Kepok Banana Peel Extract (3000 mg/kg BB) of 43.88%. Varying doses of kepok banana peel extract (Musa paradisiaca L.) had an influence on analgesic activity in male mice (Mus musculus) with a p value of 0.001 (<0.05). Keywords: Analgesic, Hot plate, Mus musculus, Musa paradisiaca L.